2020
DOI: 10.1007/s42452-020-2115-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma ray on some properties of bismuth borate glasses containing different transition metals

Abstract: This work aims to study the influence of gamma irradiation on some bismuth borate glasses doped with different transition metal oxides (CuO, CoO, ZnO and CdO). The structure of the glass matrix was analyzed by Fourier transform infrared and ultraviolet-visible spectroscopy before and after gamma irradiation at doses of 1 kGy, 20 kGy and 50 kGy. Additionally, the attention is made in determining the attenuation parameters against gamma rays. Mass attenuation coefficient determined experimentally and calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The increase in density is due to the higher values of the molecular weight of PbO. The hardness results showed higher hardness values for samples containing PbO and this may be due to shortening of the bonds leading to more bond strength [10].…”
Section: Hardness and Density Measurementmentioning
confidence: 95%
See 1 more Smart Citation
“…The increase in density is due to the higher values of the molecular weight of PbO. The hardness results showed higher hardness values for samples containing PbO and this may be due to shortening of the bonds leading to more bond strength [10].…”
Section: Hardness and Density Measurementmentioning
confidence: 95%
“…The linear attenuation is better in lower energy than above, as shown in Fig. 5 The mass attenuation coefficients were calculated from the intensity of the measured incident gamma-rays and the intensity of transmittal gamma-rays [10] Table…”
Section: Gamma Ray Attenuation Coefficientsmentioning
confidence: 99%
“…The previous researchers Sahar A.El-Ghany et al (2020) (13) , investigated the effect of gamma ray irradiation on structural, physical and optical properties of bismuth borate glasses containing different transition metals. But gamma ray irradiation effect on AC conductivity has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their high atomic number, these glasses emerge as potential materials in optics, nuclear technology, and in the field of superconductors [ 24 , 25 ]. Reports show that many glasses are known to fulfill these requirements, based on the recent investigation of different glass compositions for their radiation shield competence [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. In order to study luminescence parameters such as stimulated emission cross section and branching ratios, five glass samples having the composition 47.5P 2 O 5 +45ZnO+(5-x)Bi 2 O 3 +2.5TeO 2 +xSm 2 O 3 (where x = 0, 0.01, 0.1, 0.3, 0.5 and 1 mol%) were prepared and found that color vanishes with a minimal amount of Sm 2 O 3 [ 23 ].…”
Section: Introductionmentioning
confidence: 99%